Influence of education on cognitive function in the elderly population of Pune city, Maharashtra, India - Godbole, Shrirang; Godbole, Gayatri; Vaidya, Savita (International Journal of Research in Medical Sciences, 2016)
Background: A progressive decline in cognitive function is called as dementia. It mostly affects the elderly population. Dementia places a great burden on the patient, on his family and also on the country’s healthcare system. It has therefore become the need of the day, to combat its ever increasing prevalence. Methods: In this community based study, 300 Residents (males and females) aged 60 years and above were interviewed. Subjects were administered mini mental state examination (MMSE) questionnaire. MMSE score of <23 indicates the likelihood of cognitive impairment. Educational status of the subjects with MMSE score <23 was compared. Results: Level of education was negatively correlated with MMSE score and it was statistically significant. Conclusions: Education is an important factor in mitigating the effects of dementia. Early investment in education will go a long way installing the progress of dementia.